ND3 Cys39 in complex I is exposed during mitochondrial respiration. Issue 4 (21st April 2022) - Burger, Nils; James, Andrew M.; Mulvey, John F.; Hoogewijs, Kurt; Ding, Shujing; Fearnley, Ian M.; Loureiro-López, Marta; Norman, Abigail A.I.; Arndt, Sabine; Mottahedin, Amin; Sauchanka, Olga; Hartley, Richard C.; et al.
Summary: Mammalian complex I can adopt catalytically active (A-) or deactive (D-) states. A defining feature of the reversible transition between these two defined states is thought to be exposure of the ND3 subunit Cys39 residue in the D-state and its occlusion in the A-state. As the catalytic A/D transition is important in health and disease, we set out to quantify it by measuring Cys39 exposure using isotopic labeling and mass spectrometry, in parallel with complex I NADH/CoQ oxidoreductase activity. To our surprise, we found significant Cys39 exposure during NADH/CoQ oxidoreductase activity. Furthermore, this activity was unaffected if Cys39 alkylation occurred during complex I-linked respiration. In contrast, alkylation of catalytically inactive complex I irreversibly blocked the reactivation of NADH/CoQ oxidoreductase activity by NADH. Thus, Cys39 of ND3 is exposed in complex I during mitochondrial respiration, with significant implications for our understanding of the A/D transition and the mechanism of complex I. Graphical abstract: Highlights: ND3-Cys39 in complex I is exposed during active mitochondrial respiration Modification of exposed Cys39 in active complex I does not impair respiration Modification of exposed Cys39 in deactive complex I prevents reactivation Complex I activity and Cys39 exposure are not linked directly Abstract : The enigmatic active/deactive transition of complex I is linked to the exposure state of the critical ND3-Cys39 residue, functioning as critical indicator. Burger et al. show that Cys39 is exposed during complex I-linked respiration with important implications for the understanding of the active/deactive transition and complex I function.